The Architecture of Contemporary Care Networks for Rare Movement Disorders: Leveraging the ParkinsonNet Experience - van de Warrenburg, Bart P.; Tiemessen, Mark; Munneke, Marten; Bloem, Bastiaan R. (Frontiers in Neurology, 2021)
In this paper, we present a universal model for implementing network care for persons living with chronic diseases, specifically those with rare movement disorders. Building on our longstanding experience with ParkinsonNet, an integrated care network for persons living with Parkinson's disease or a form of atypical parkinsonism, we provide a series of generic, supportive building blocks to (re)design comparable care networks. We discuss the specific challenges related to rare movement disorders and how these challenges can inform a tailored implementation strategy, using the basic building blocks to offer practical guidance. Lastly, we identify three main priorities to facilitate network development for these rare diseases. These include the clustering of different types of rare movement disorders at the network level, the implementation of supportive technology, and the development of interdisciplinary guidelines.